Tax Ratio and Degree of Regional Fiscal Autonomy Moderate Effect of Economic Growth on Human Development Index - I Gede Eka Witanaya Partha; A.A.N.B Dwirandra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to obtain empirical evidence of the effect of economic growth on the human development index (HDI) in the districts and cities of Bali Province in 2014–2019 by including the tax ratio and the degree of regional fiscal autonomy as moderating variables. The research was conducted in all regencies and cities in Bali Province. The data in this study were obtained from the Central Bureau of Statistics which were tested using moderated regression analysis. The results of this analysis indicate that economic growth has a positive effect on HDI and the influence of HDI cannot be moderated by the tax ratio. This study also finds that the effect of economic growth on HDI is strengthened by the degree of regional fiscal autonomy. Regional autonomy is able to increase economic growth which can be achieved with a degree of regional fiscal autonomy through the implementation of regional autonomy. On the other hand, the tax ratio may not necessarily increase the HDI level due to the uneven development associated with the increase in HDI in the Province of Bali.